2012
DOI: 10.1124/mol.112.079699
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening for LPA2-Specific Agonists Identifies a Nonlipid Compound with Antiapoptotic Actions

Abstract: Lysophosphatidic acid (LPA) is a highly potent endogenous lipid mediator that protects and rescues cells from programmed cell death. Earlier work identified the LPA 2 G proteincoupled receptor subtype as an important molecular target of LPA mediating antiapoptotic signaling. Here we describe the results of a virtual screen using single-reference similarity searching that yielded compounds 2-((9-oxo-9H-fluoren-2-yl) carbamoyl)benzoic acid (NSC12404), 2-((3-(1,3-dioxo-1H-benzo- [de]isoquinolin-2(3H)-yl)propyl)th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 41 publications
0
48
0
Order By: Relevance
“…1b). Because GRI977143 is both a selective agonist of the LPA 2 receptor and a weak antagonist of LPA 3 (Kiss, et al, 2012), we also examined whether DBIBB had antagonist or allosteric modulatory action on LPA 1/3/4/5 GPCR. The pharmacological characterization of DBIBB at LPA 2 showed that had nanomolar potency (IC 50 ~100 nM, a 33-fold increase over GRI977143); it was a specific agonist without activating or inhibiting LPA 1/3/4/5 receptors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b). Because GRI977143 is both a selective agonist of the LPA 2 receptor and a weak antagonist of LPA 3 (Kiss, et al, 2012), we also examined whether DBIBB had antagonist or allosteric modulatory action on LPA 1/3/4/5 GPCR. The pharmacological characterization of DBIBB at LPA 2 showed that had nanomolar potency (IC 50 ~100 nM, a 33-fold increase over GRI977143); it was a specific agonist without activating or inhibiting LPA 1/3/4/5 receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, improved non-lipid, drug-like analogs specific to the LPA 2 GPCR could provide drug candidates suitable for the treatment of ARS. In silico drug discovery has identified 2-((3-(1,3-dioxo-1 H -benzo[ de ]isoquinolin-2(3 H )-yl)propyl)thio)-benzoic acid ( GRI977143 ) nonlipid compound that activates LPA 2 selectively although not specifically (Kiss, et al, 2012). GRI977143 , however, lacks the desired drug-like potency; it also has compromised specificity because it is an antagonist of LPA 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The ability of LPA and LPA receptor agonists to protect multiple cell types against SD/H, 104 combined with the relatively low cost, makes them ideal for many cell delivery applications. Micromolar concentrations of LPA protect neuronal precursors, 105 osteoblasts, osteoclasts, 88 rat and human MSCs, 4,5 and other cell types against SD/ H-and endoplasmic reticulum-stress induced apoptosis in vitro in a pertussis toxin-and PI3K-dependent manner.…”
Section: Pharmacological Strategies For Inhibiting Apoptosis and Prommentioning
confidence: 99%
“…Some of these hit optimization studies have been driven by structure-based design Congreve et al 2012;Lin et al 2012;Becker et al 2006;Wacker et al 2010). One of the most frequently observed steps in a VS hit exploration is the search for close analogues of one or more hit compounds (Carlsson et al 2010(Carlsson et al , 2011Langmead et al 2012;Kim et al 2012;Kiss et al 2012) or to synthesize a small series around one or more hit compounds Yrjola et al 2013) (Table 7.2). The experimental validation of compound 8, an AA2AR-selective VS hit from Carlsson et al (2010), was followed by an analogue search which yielded 5 equally selective analogues but all with a lower affinity.…”
Section: Optimization Of Virtual Screening Hitsmentioning
confidence: 99%